Magnetic properties and magnetocaloric effects of Gd65(Cu, Co, Mn)35 amorphous ribbons. Issue 10 (October 2019) - Jia, Peng; Duan, Leipeng; Wang, Kang; Wang, Engang
Abstract: The magnetic phase transition and magnetocaloric effects of Gd65 (Cu, Co, Mn)35 amorphous ribbons were investigated. The increased Mn substitution for Co or Mn substitution for Cu led into a higher second-order magnetic phase transformation temperature, near 200 K in all ribbons. Under the field change of 7 T, a maximum entropy change (Δ S m max ) of 6 J kg −1 K −1 was achieved in Gd65 Cu10 Co20 Mn5 ribbon and slightly dependent on the compositions. With varied composition, a full width at half of Δ S m max was greatly widened to be over than 180 K for Gd65 Cu15 Co10 Mn10 ribbon. The refrigeration capacity was also greatly enhanced to 1000 J kg −1 for Gd65 Cu20 Co10 Mn5 ribbon, which was even excellent compared with other Gd-based amorphous systems.